2022
DOI: 10.1002/asia.202200503
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol‐derived Organic Liquids as an In‐Situ CO2 Capturing and Conversion System for Eugenol‐based Polycarbonate Synthesis

Abstract: The significant development of catalytic biomass conversion has provided a large library of chemicals ready for subsequent upgrading to polymerisable monomers for the design and preparation of sustainable polymers. In this study, hydroxyethylation of eugenol by using green ethylene carbonate as alkylation reagent and cheap tetrabutylammonium iodide ionic liquids as green solvents and catalysts produced 2-(4-allyl-2-methoxyphenoxy)ethan-1-ol with a 85% yield, which could be used to construct an in situ CO 2 cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Lignin is the most abundant natural aromatic polymer resources on earth, and the catalytic biorefinery of lignin produced a large spectrum of aromatic chemicals, such as vanillin, vanillic acid, guaiacol, and eugenol. [36][37][38] Vanillin is a natural phenolic aromatic compound from the pods of an orchid, considering as one of the most important flavors around the world. [39] Now, the vanillin is even produced from lignin at an industrial scale.…”
Section: Introductionmentioning
confidence: 99%
“…Lignin is the most abundant natural aromatic polymer resources on earth, and the catalytic biorefinery of lignin produced a large spectrum of aromatic chemicals, such as vanillin, vanillic acid, guaiacol, and eugenol. [36][37][38] Vanillin is a natural phenolic aromatic compound from the pods of an orchid, considering as one of the most important flavors around the world. [39] Now, the vanillin is even produced from lignin at an industrial scale.…”
Section: Introductionmentioning
confidence: 99%
“…The pioneering work by Jessop demonstrated that reversible capture of CO 2 can be achieved in the presence of organic base and proton donor solvents . Recently, we applied this methodology to prepare α,ω-diene-functionalized carbonate monomers, which were converted to polycarbonates via thiol–ene and ADMET polymerization. , Notably, when amine was employed as a proton donor, nucleophilic RNHCOO – was formed, which could react with haloalkanes, leading to novel carbamates. Herein, taking advantage of the reversible reaction of CO 2 with diamines in the presence of organic bases, we introduce a toolbox for in situ capturing and conversion of CO 2 into polymerizable carbamates, which were converted to NIPUs via thiol–ene and ADMET polymerization.…”
mentioning
confidence: 99%